Upaya Meningkatkan Hasil Belajar Matematika Dengan Menggunakan LKS Untuk Siswa Kelas IV SD Negeri 012 Rambah Hilir - Widayati Widayati (STKIP Rokania Pasir Pangaraian, 2018)
Learning is gathering knowledge, knowledge gained from someone who knows or is known as a teacher. His many learned people are identified as people with a lot of knowledge. In the complete dictionary of Indonesian language (2003: 279) learning is to strive for certain intelligence and knowledge by considering that these actions will be sought by certain results and will be of interest to these people. The basic principle that makes students feel comfortable because there is no process used for actions that may not be something that will be considered or understood by the items given by the teacher. LKS is a student worksheet designed by both individual and group teachers, where the student worksheets are made in accordance with the work procedures that will be carried out by the tools and materials provided by the school or teacher and to carry out the learning. LKS is made from the subject matter that will be studied, the purpose of the worksheet, the fields to be carried out by students based on the information learned. Therefore, you can research on this subject by demanding responsibilities and collecting assignments. When the teaching and learning process takes place, the author will see more, begin to be active and think in various actions. However, after being taught, the author did not feel satisfied with the results of student learning, which came from 28 students who were still incomplete with KKM 65